Curcumin-enhanced NIR-II-responsive gold nanobipyramids for targeted HSP 90 inhibition - Zhenying Diao; Youcheng Liang; Yong Liu; Dou Zhang; Long Qiu; Jianbo Sun; Qiaoyou Lu; Yanlei Liu; Daxiang Cui; Ting Yin (Materials Today Bio)
Blockade of heat shock protein 90 (HSP90) expression in multimodal synergistic therapy has a great prospect for cancer treatment. Nanomaterials combined with bioinformatic analysis provides accurate guidance for the design of anti-HSP90 nanomedicines. Herein, a NIR-II-responsive nanoplatform was developed under bioinformatics guided to effectly inhibit HSP90 for enhanced synergistic mild-photothermal chemotherapy without any notable tissue damage. The nanoplatforms were assembled from NIR-II-responsive gold nanobipyramids (GNBs) combined with curcumin (Cur) via hydrophobic-hydrophobic interactions and hydrogen bonds. On the basis of drug discovery and network pharmacology, we found that Cur has impressive anti-HSP90 capability and analyzed its therapeutic mechanism against NSCLC. Under the irradiation of NIR-II light, the obtained GNBs-Cur blocked the expression of HPS90 and inhibited related antiapoptotic pathways, thus enhancing the mild PTT of GNBs under 1064 nm laser irradiation. Meanwhile, Cur served as chemotherapeutic agents to induce apoptosis in tumor cells. In vivo photoacoustic imaging-guided, GNBs-Cur achieved effective tumor elimination through mild-photothermal chemotherapy without systemic toxicity. Overall, this work provides a new therapeutic modality paradigm for potential NSCLC treatment on the basis of synergistic therapies.